2022
DOI: 10.1111/jocd.15457
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of perceived quality on consumer attitudes and satisfaction: Focus on lip products

Abstract: Background Growth of national and economic development industrial and economic standards has raised women's social status, and the consumption value of aesthetic pursuit, which is the mainstream among women's diverse needs as consumers, has been increasing in quantities. Aim This study attempted to investigate what are the consumer selection criteria for lip products represented by the lipstick effect that creates continuous demand even in the COVID‐19 era, and the main factors driving the continuous demand fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…1, which mainly reflects the actual feelings of users on the quality and performance of vehicles' hardware. Lim and Ozkan et al demonstrated that in daily consumption products, product quality has a significant positive impact on customers' attitudes and satisfaction [40,41]. Agyeman et al revealed a strong relationship between the perceived quality and school bus services' accessibility, safety, efficiency, and other factors [42].…”
Section: Construct Definition and Hypothesis Developmentmentioning
confidence: 99%
“…1, which mainly reflects the actual feelings of users on the quality and performance of vehicles' hardware. Lim and Ozkan et al demonstrated that in daily consumption products, product quality has a significant positive impact on customers' attitudes and satisfaction [40,41]. Agyeman et al revealed a strong relationship between the perceived quality and school bus services' accessibility, safety, efficiency, and other factors [42].…”
Section: Construct Definition and Hypothesis Developmentmentioning
confidence: 99%
“…Hal ini bisa memicu tingkat penjualan tidak stabil. Oleh karena itu, perusahaan dituntut untuk tetap mengutamakan kualitas produk yang dijual untuk tetap bisa memuaskan pelanggannya (Asha, 2023;Bhowmick, 2023;Ekasari, 2019;Febryanto, 2018;Hallencreutz, 2021;Lim, 2022;Poornachandrika, 2020;Soegoto, 2018;Venkatasudhahar, 2023).…”
Section: Pendahuluanunclassified